Role of Vitamin E and Vitamin A on Severity of Oral Mucositis Caused by Chemotherapy - A Randomized Double-Blind Cross-Over Clinical Trial - Gholami, Hossein; Ahrari Roodi, Tahereh; Mohamadifard, Mohamad Amir; Alizadeh, Leili (UI Scholars Hub, 2024)
Objective: This study aimed to evaluate the efficacy of these vitamins in reducing chemotherapy-induced oral mucositis through a randomized, double-blind, cross-over clinical trial. Methods: This study involved 20 participants, primarily female (70%), with an average age of 52.2 years. Participants first received oral vitamin E and A with chemotherapy, followed by a placebo. The severity of mucositis and pain responses were assessed at the start of the study and at 7-, 14-, and 21-day post-treatment initiation. Data analysis was performed using SPSS software with a significance level of 0.05. Results: Twenty patients,14 (70%) females, with a mean age of 52.2 ± 14.37, completed the study. Results indicated no significant relationship between treatment type and mucositis severity at baseline (p = 0.890) and no notable differences in severity between the vitamin and placebo periods (p > 0.05). Additionally, no significant variations in mucositis severity or pain responses were observed throughout the study duration (p > 0.05). Conclusion: In conclusion, oral supplementation of vitamins E and A did not significantly reduce the severity of chemotherapy-induced oral mucositis or alleviate associated pain in participants.